Pain in the Past and Pleasure in the Future: The Development of Past–Future Preferences for Hedonic Goods. Issue 9 (30th August 2020) - Lee, Ruth; Hoerl, Christoph; Burns, Patrick; Fernandes, Alison S.; O'Connor, Patrick A.; McCormack, Teresa
Abstract: It seems self‐evident that people prefer painful experiences to be in the past and pleasurable experiences to lie in the future. Indeed, it has been claimed that, for hedonic goods, this preference is absolute (Sullivan, 2018). Yet very little is known about the extent to which people demonstrate explicit preferences regarding the temporal location of hedonic experiences, about the developmental trajectory of such preferences, and about whether such preferences are impervious to differences in the quantity of envisaged past and future pain or pleasure. We find consistent evidence that, all else being equal, adults and children aged 7 and over prefer pleasure to lie in the future and pain in the past and believe that other people will, too. They also predict that other people will be happier when pleasure is in the future rather than the past but sadder when pain is in the future rather than the past. Younger children have the same temporal preferences as adults for their own painful experiences, but they prefer their pleasure to lie in the past and do not predict that others' levels of happiness or sadness vary dependent on whether experiences lie in the past or the future. However, from the age of 7, temporal preferences were typically abandoned at the earliest opportunity when the quantity of past pain or pleasure was greater than the quantity located in the future. Past–future preferences for hedonic goods emerge early developmentally but are surprisingly flexible.